Analisa Analisis korelasi antara kualitas air dan identifikasi mikroplastik di wilayah pesisir utara Situbondo. - Arisda Maryama Santikanuri; Riyanto Haribowo; Sri Wahyuni (Postgraduate, University of Mataram, 2025)
Water pollution occurs when unwanted substances contaminate a body of water, affecting its quality. Rivers, as the main source of water, are particularly vulnerable to pollution from human activities. This study was located in the Situbondo North Coast Area with a focus on 15 sampling points. Water quality was assessed through several parameters. The abundance and characteristics of microplastics were analyzed, revealing the highest abundance at one point, with small fiber-shaped black particles predominant. Canonical Correspondence Analysis (CCA) identified microplastic characteristics, such as color and size, showed strong correlations with water quality. Green and large-sized microplastics were associated with increased ammonia and turbidity, while transparent and fragmentary microplastics correlated with decreased DO and increased BOD. Black microplastics were associated with a decrease in pH. These findings confirm the role of microplastics in worsening the chemical and biological conditions of waters. The study also found that Dissolved Oxygen (DO) and BOD had the strongest influence on the relationship between water quality and microplastics, highlighting the ecological significance of these findings.